Optimizing Material Selection and Manufacturing Processes For Enhanced Drill Bit Performance - Syaputra, Robby Yandri; Barimbing, Ivan Mangisara; Syaputra, Muhammad Lyan; Borutnaban, Bernath Matheus; hasibuan, fardin; Irsyam, Muhammadd (Universitas Riau Kepulauan, 2025)
Drill bit performance is significantly influenced by material selection and manufacturing processes. This study optimizes material choices and advanced manufacturing techniques to enhance drill bit performance. By evaluating mechanical properties, wear resistance, and thermal stability of various materials, the research identifies the most suitable options for specific drilling conditions. Additionally, the impact of advanced manufacturing methods, such as additive manufacturing and precision machining, is explored to improve accuracy, durability, and efficiency. The results demonstrate improvements in drill bit performance, including reduced wear and extended operational lifespan. This research contributes to the development of more efficient and durable drill bits.